Electrosurgical technology: Quintessence of the laparoscopic armamentarium - Deeksha Pandey; Chih-Feng Yen; Chyi-Long Lee; Ming-Ping Wu (Wolters Kluwer Medknow Publications, 2014)
One of the biggest enemies of minimally invasive surgery is bleeding. The ongoing desire to improve hemostasis and thus its efficacy has led to the rapid evolution of electrosurgical technology. In this review we discuss the yet evolving science of electrosurgery. For the optimal use of available tools, it is of utmost importance for the laparoscopic surgeon to understand that different electrosurgical instruments have different properties and thus their use has to be tailored. To understand the concept well, we review the important landmarks in the evolution of electrosurgery related to gynecological laparoscopy, revisit the basic principles, and then proceed on to discuss the modern tools in the electrosurgical armamentarium.